2020
DOI: 10.1049/iet-epa.2019.0483
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field‐modulated linear permanent‐magnet generator for direct‐drive wave energy conversion

Abstract: The linear permanent-magnet synchronous generator (LPMSG) for direct-drive wave energy conversion (WEC) suffers from many drawbacks that have not yet been overcome, such as a low power density and a bulky system volume. Therefore, a magnetic field-modulated linear permanent-magnet generator (FMLPMG) with a simple structure has been designed and manufactured. First, the operating principle of the FMLPMG is demonstrated by the equivalent magnetic circuit method, which explains the high power density of the FMLPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Refine design parameters for permanent magnet shape modification of … (Noor Syazana Abd Ghani) 137 increases, as supported by the findings of [23]- [25]. The findings demonstrated that the back-EMF reached the induced voltage produced to have the output power at the pico-scale.…”
Section: Influence Of Split Ratio 𝑹𝒎/𝑹𝒆mentioning
confidence: 59%
See 1 more Smart Citation
“…Refine design parameters for permanent magnet shape modification of … (Noor Syazana Abd Ghani) 137 increases, as supported by the findings of [23]- [25]. The findings demonstrated that the back-EMF reached the induced voltage produced to have the output power at the pico-scale.…”
Section: Influence Of Split Ratio 𝑹𝒎/𝑹𝒆mentioning
confidence: 59%
“…𝐿 𝑠 /𝐿 𝑟 influenced the magnetic flux that passed through the coil and was correlated with the voltage induced by the coil. The leading parameter of 𝜏 𝑚𝑟 /𝜏 𝑝 ratio reflected the combined effects of radially and axially magnetized magnets to achieve a maximum fundamental radial flux density in the air gap [23]- [26]. The dimension sizes of all the permanent magnet designs were different due to the different shapes of the permanent magnets used during the designing process.…”
Section: Refine Design Parametermentioning
confidence: 99%
“…Moreover, the generator performances have been analysed in no-load and load conditions and for single-phase and 3-phase [93]. Moreover, the simulations have been performed for the no-load and load condition [177].…”
Section: Numerical Analysismentioning
confidence: 99%
“…In addition, in order to adapt the ocean environment of D-DWEC system, refs. [74,75] have studied two types of linear generators with integrated magnetic gear respectively, and the purpose is to have simple structure, simple processing, high reliability and low cost.…”
Section: Linear Magnetic Gearmentioning
confidence: 99%